Member Cooperative Learning Model for Strengthening Cooperative Principles at Artha Kencana Cooperative, Cangkir Village, Driyorejo District, Gresik Regency - Rachman Halim Yustiawan; Titin Titin; Sirojul Munir; Dwi Nur Nikmah; Sri Kurnia Abdi Pradhana (Jurnal Multidisiplin Sahombu, 2026)
Village cooperatives frequently face limited member literacy, weak participation, incomplete governance documentation, and low digital readiness. This study evaluates a Member Cooperative Learning (MCL) model designed to strengthen cooperative principles and institutional performance at Artha Kencana Cooperative in Cangkir Village, Gresik Regency. A descriptive qualitative design with a participatory research approach involved 90 members selected purposively from approximately 200 members across four business units. Data were collected through educational workshops, focus group discussions, simulations, participatory observation, interviews, document review, and a pre-test/post-test questionnaire covering cooperative identity, member rights and responsibilities, democratic governance, financial administration, and collective marketing. Quantitative evaluation data were summarized descriptively, while interview, observation, and document data were analyzed thematically and triangulated. Before the program, only about 30% of participants demonstrated adequate understanding of cooperative principles. After the intervention, 50.0% achieved a high knowledge category and 38.9% a moderate category. Participation in the Annual Members' Meeting exceeded 75%, three core governance documents were established, marketing channels expanded from one to at least three, average monthly sales increased from IDR 5.0 million to IDR 7.5 million, and the proportion of members operating independent or joint businesses rose from about 20% to more than 50%. The study contributes an integrated learning model that connects cooperative education with governance practice, digital financial recording, product marketing, and women's economic empowerment. Because the study involved one cooperative without a control group, the outcomes should be interpreted as program-associated improvements rather than definitive causal effects.